Contextual factors influencing early return to work in the rural and remote sector - Ciccarelli, Marina; Dender, J. (Curtin Business School, Curtin University of Technology, 2010)
Early return to work (RTW) interventions are important in facilitating successful and timely resumption of the worker role following a work-related injury. Early RTW strategies include strong communication between the employer, injured worker and treating physician; maintenance of the worker role, and accommodation of the injured worker through the provision of suitable alternative duties and modification of the workplace. In the State of Western Australia, all regions beyond the capital city are considered rural and remote. Workplace rehabilitation providers working in rural and remote regions face unique challenges in implementing early RTW interventions for injured workers due to issues of geographic distance, work cultures and limited availability of alternative jobduties. This paper discusses some of the factors restricting early RTW interventions and possible strategies to overcome these hurdles.